Analisis Perbedaan Kinerja Keuangan Bank Syariah Menurut Standar AAOIFI - Jhody Wiraputra; Okta Sari; Ridwansyah, Ridwansyah (Journal of Islamic Economic Studies, 2025)
This study aims to qualitatively analyze the differences arising in the measurement of financial performance of Islamic banks when measured using AAOIFI Financial Accounting Standards compared to accounting standards in force in Indonesia. This study uses qualitative research library studies with content analysis and comparative interpretation to understand the philosophical and practical impact of standard differences on key performance indicators. The results of the analysis indicate that the measurement of the financial performance of Islamic banks will be materially different when using the AAOIFI framework compared to PSAK Syariah, mainly due to differences in the philosophy of AAOIFI standards oriented to Sharia normative compliance, while PSAK oriented to economic decision-making. This key divergence affects the calculation of profitability ratios and AAOIFI's emphasis on social reporting as well as comprehensive sharia compliance audits, so that AAOIFI provides a more holistic and accurate picture of performance in accordance with the objectives of Maqashid Sharia. The implication of this study is that Islamic banks in Indonesia need to consider harmonizing their financial reporting standards towards the AAOIFI framework to achieve more accurate, holistic, and aligned performance transparency with the principles of Maqashid Sharia, in order to improve global competitiveness.